2011
DOI: 10.1061/(asce)gt.1943-5606.0000525
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Volatile Organic Compounds Diffusion for Virgin Geosynthetic Clay Liners and for a GCL after Contact with a Synthetic Leachate

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Their results indicate that bulk-GCL void ratios ranging from 4.1 to 4.8 correspond to low normal stress and that the corresponding diffusion coefficients represent an upper bound for diffusion coefficients. In further studies, Rosin-Paumier et al (2011) reported that the composition of the bentonite (natural sodium versus calcium-activated) has no significant impact on the diffusion of VOCs. At 23 C, the diffusion coefficients for VOCs in bentonite range from 1 to 3 Â 10 À10 m 2 /s for bulk-GCL void ratios ranging from 3.7 to 4.8.…”
Section: Diffusion Of Organic Species Through Geosynthetic Clay Linersmentioning
confidence: 95%
“…Their results indicate that bulk-GCL void ratios ranging from 4.1 to 4.8 correspond to low normal stress and that the corresponding diffusion coefficients represent an upper bound for diffusion coefficients. In further studies, Rosin-Paumier et al (2011) reported that the composition of the bentonite (natural sodium versus calcium-activated) has no significant impact on the diffusion of VOCs. At 23 C, the diffusion coefficients for VOCs in bentonite range from 1 to 3 Â 10 À10 m 2 /s for bulk-GCL void ratios ranging from 3.7 to 4.8.…”
Section: Diffusion Of Organic Species Through Geosynthetic Clay Linersmentioning
confidence: 95%
“…The diffusion also depends on temperature, with lower value at a relatively lower temperature [89]. What is noteworthy is that, by contrast with the influence on hydraulic conductivity of GCLs, the type of bentonite contained in GCLs (sodium or calcium) and the ion exchange in bentonite (e.g., from sodium to calcium) both have no obvious influence on the diffusion coefficient of GCLs [90,92]. The diffusion coefficient can be also significantly influenced by the concentration level of the solute, which is able to modify the microstructure of the sensitive minerals [86].…”
Section: Diffusionmentioning
confidence: 97%
“…The diffusion coefficients for different chemical molecules or ions through GCLs can vary a lot. Lake and Rowe (2004) [23] coefficient have been proposed [88][89][90]. The test involves placing a contaminant source solution on one side of a GCL specimen and an uncontaminated receptor solution on the other side (see Figure 8).…”
Section: Diffusionmentioning
confidence: 99%
“…Values of diffusion coefficients for NaB used in geoenvironmental containment barriers have been measured in the laboratory using a variety of methods (e.g., steady-state, time-lag, column, half-cell, double-reservoir; see Shackelford 1991). Over the last few decades, there has been an emphasis in the literature on evaluation of diffusion through NaB in GCLs (e.g., Lake and Rowe 2000;Rowe et al 2000;Malusis and Shackelford 2002;Lange et al 2009;Paumier et al 2011;Malusis et al 2015;Saheli and Rowe 2016;Shackelford et al 2016;Sample-Lord et al 2017;Dominijanni et al 2018). Laboratory-measured values of D a and D* for tests performed on NaB GCLs with simple salt solutions (e.g., NaCl, KCl, CaCl 2 ) are typically on the order of 10 À11 to 10 À9 m 2 /s, and several studies have reported generally increasing values of D a and D* with increasing ionic strength and cation valence of the solution in the pore water of the bentonite (e.g., Malusis and Shackelford 2002;Lange et al 2009;Shackelford et al 2016;Dominijanni et al 2018).…”
Section: Diffusion Coefficients Of Bentonitementioning
confidence: 99%